Priorities And Basic Trends In State Social Policy Aimed At Reducing Poverty In Uzbekistan And The Main Directions Of Expulsion Of Economic Insolvent - Khujanov Zafar Bektemirovich (Genius Journals, 2023)
In this article, we will mention a number of issues about the fact that several works are being carried out aimed at reducing the poverty of our state, finding its solutions , increasing jobs and eliminating all public and serious problems, a number of works, plans and solutions, on the surface of its manifestations, a large number of taxs and negotiations are being carried out. At the same time , it will not be a lie if we emphasize that this problem is one of the main problems not only of our state, but of the whole world.
Keywords: Mention; several works; solutions; whole world